Pengaruh Intensitas Kebisingan Dengan Tekanan Darah Pekerja Sukarelawan Pembantu Lalu Lintas Kota Makassar - Suryadi, Iwan; Kasim, Khiki Purnawati; Rostina (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Makassar, 2023)
Work environment factors are one of the factors that cause success in carrying out work but can also cause failure in carrying out a job, because the work environment can affect the physical and mental conditions of workers. One of the factors of the work environment is exposure to noise. Exposure to noise can cause health problems such as increased blood pressure. This study used an analytic observational study with a cross sectional approach. The number of samples is 102 respondents obtained by means of simple random sampling. Measuring noise intensity using a sound level meter and blood pressure using a blood pressure meter. Individual characteristics are assessed using a questionnaire. The results showed that there was an effect of exposure to noise intensity on systolic and diastolic blood pressure with p-values of 0.001 and 0.048 and r-values of 0.329 and 0.192 respectively. There is a strong and unidirectional relationship between noise exposure and blood pressure. This increase in blood pressure can be controlled with hearing conservation such as regular hearing tests. Keywords : Noise intensity, blood pressure